2016
DOI: 10.1080/14737175.2016.1203256
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and cognitive disorders: a systematic review of the clinical evidence

Abstract: Preclinical and clinical evidence suggest an association between anesthesia and cognitive disorders ranging from postoperative chronic dysfunction to Alzheimer's disease. Recent clinical insights are summarized in this paper. Areas covered: This systematic review was conducted and written in accordance with the preferred reporting items for systematic reviews and meta-analyses statement and was registered in the International Prospective Register of Systematic Review database. A literature search of PubMed, EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…Despite the debatable cause of POCD syndromes, it remains a perioperative priority that demands all plausible factors to be considered for lowering its incidence. Amongst the many predisposing factors, the choice of anesthetic agent/technique represents a likely one [ 83 , 84 ].…”
Section: Elderly and Cognitionmentioning
confidence: 99%
“…Despite the debatable cause of POCD syndromes, it remains a perioperative priority that demands all plausible factors to be considered for lowering its incidence. Amongst the many predisposing factors, the choice of anesthetic agent/technique represents a likely one [ 83 , 84 ].…”
Section: Elderly and Cognitionmentioning
confidence: 99%
“…Furthermore, AD patients are more susceptible to development of cognitive function decline after anesthesia and surgery . Repeated exposure to general anesthetics, such as isoflurane, is a potential risk factor for development of POCD and AD . Furthermore, high level of Aβ in aging brain following general anesthetic exposure is likely to increase the risk of the POCD development .…”
Section: Introductionmentioning
confidence: 99%
“…The traditional anesthesia (e.g., isoflurane-mediated anesthesia) increases the risk of AD (15)(16)(17). Some traditional anesthetic agents are associated with AD pathogenesis (18). Behavioral tests in rodent models showed that a transient exposure to anesthetic drug isoflurane caused a lasting impairment to the cognition (15,16,19).…”
Section: Introductionmentioning
confidence: 99%